Estimating the effect of government programs on youth entrepreneurship in the Philippines - Rivera, John Paolo R. (Animo Repository, 2019)
For decades, the majority of the Philippines’ jobless sector is comprised of the youth. This creates the need to craft programs and policies that would enable entrepreneurship among Filipino youths. Using the Community Based Monitor System survey on Accelerated Poverty Profiling among member schools of De La Salle Philippines, we estimate the marginal effects of a multinomial logistic regression that underscore how participation in government-sponsored programs impacts a youth’s likelihood to be entrepreneurial. Results suggest a framework for improving program design and policy implementation to support youth entrepreneurial undertakings. © 2019 by De La Salle University.